Structure and function of the Zika virus full-length NS5 protein - Zhao, Baoyu; Yi, Guanghui; Du, Fenglei; Chuang, Yin-Chih; Vaughan, Robert C.; Sankaran, Banumathi; Kao, C. Cheng; Li, Pingwei (Nature communications, 2017)
The recent outbreak of Zika virus (ZIKV) has infected over 1 million people in over 30 countries. ZIKV replicates its RNA genome using virally encoded replication proteins. Nonstructural protein 5 (NS5) contains a methyltransferase for RNA capping and a polymerase for viral RNA synthesis. Here we report the crystal structures of full-length NS5 and its polymerase domain at 3.0 Å resolution. The NS5 structure has striking similarities to the NS5 protein of the related Japanese encephalitis virus. The methyltransferase contains in-line pockets for substrate binding and the active site. Key residues in the polymerase are located in similar positions to those of the initiation complex for the hepatitis C virus polymerase. The polymerase conformation is affected by the methyltransferase, which enables a more efficiently elongation of RNA synthesis in vitro . Overall, our results will contribute to future studies on ZIKV infection and the development of inhibitors of ZIKV replication. Zika virus infection can cause human birth defects and Guillain-Barré syndrome. Here the authors present the structures of the full-length nonstructural protein 5 and its RNA-dependent RNA polymerase domain of Zika virus, which are targets for inhibitors of virus replication.